A temática gênero nos projetos de lei de mulheres parlamentares da Assembleia Legislativa de Goiás (2015-2022) - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
Gender disparity, both socially and politically, remains a persistent obstacle on the path towards a more egalitarian society. Despite the guarantee of equal rights established in the Brazilian Constitution, there is still much to be achieved in attaining gender equality. Therefore, in this research, we investigate the category of gender/sex in bills presented by female deputies in the Legislative Assembly of Goiás (Alego) during the 18th and 19th legislatures, between 2015 and 2022. We contextualize this within the backdrop of increasing conservatism in Brazil, a driver of neoliberalism, resulting in setbacks in social rights, especially those of women. This conservative movement has influenced policies, reflecting a resurgence of moralistic values and preservation of "good manners." Thus, arose the inquiry into the personal and political trajectories of female deputies in Alego during this period, and which projects they have presented, or not, to combat gender disparity in Alego. Using a qualitative documentary approach, the research aimed to explore these issues.
The Gender Theme in the Bills of Female Parliamentarians of the Legislative Assembly of Goiás (2015-2022)
Keywords: Alego; Sexo; Mulheres na política; Sex; Women in politics; CIENCIAS HUMANAS::EDUCACAO